Effects of π-conjugation on the solid-state photoresponsive coloring behavior of bipyridine–boronium complexes. Issue 11 (13th October 2020) - Yoshino, Junro; Hirono, Yoshito; Akahane, Ryota; Higuchi, Hiroyuki; Hayashi, Naoto
Abstract : The conjugation structure determined by the substitution positions of π-conjugated moieties controlled the solid-state photoinduced coloring capability of bipyridine–boronium complexes. Abstract : Solid-state photoinduced coloring of boronium complexes consisting of 9-borabicyclononane and 2, 2′-bipyridine with π-conjugated substituents at the 4, 4′- or 5, 5′-positions was investigated. The substitution position affected the highest occupied molecular orbital distribution and determined the coloring capability. The 4, 4′-substituted complexes exhibited coloration upon irradiation, whereas most of the 5, 5′-substituted complexes did not.